Correlation between Pre-Ramadan HbA1c Levels and Fasting Outcomes in Individuals with Type 2 Diabetes: Evidence from the Global 2020–2022 DAR Survey - Afandi, Bachar; Hafidh, Khadija; Ponirakis, Georgios; Habib, Mohamed; Malik, Rayaz; Alamoudi, Reem; Shaltout, Inass; Malek, Rachid; Hussein, Zanariah; Hasannien, Mohamed (Journal of Diabetes and Endocrine Practice, 2025)
Glycemic control prior to Ramadan is considered an essential determinant of fasting safety in individuals with diabetes. While the International Diabetes Federation-Diabetes and Ramadan Alliance risk calculator incorporates glycated hemoglobin (HbA1c) into fasting risk stratification, there is limited evidence to validate the cutoffs of < 7.5% and > 9% for predicting fasting outcomes.This study evaluates the association between pre-Ramadan HbA1c categories and key fasting-related outcomes in a large multinational cohort of individuals with diabetes.This subanalysis of the Diabetes and Ramadan (DaR) Global Survey categorized participants from 7 global regions covering more than 20 countries into three groups based on pre-Ramadan HbA1c: < 7.5%, 7.5 to 9%, and > 9%. Outcomes included fasting participation, hypoglycemia, hyperglycemia, and fasting interruptions due to glycemic events. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated for participants with HbA1c > 9% compared to those with HbA1c < 7.5%.Of 11,717 participants, 37.7% had HbA1c < 7.5%, 33.8% had 7.5 to 9%, and 28.5% had > 9%. Fasting participation was highest in the < 7.5% group (89.3%) and lowest in the > 9% group (80.5%; OR 0.49, 95% CI 0.43–0.56). Compared to < 7.5%, HbA1c > 9% was associated with increased odds of hyperglycemia (OR 5.10), breaking the fast due to hyperglycemia (OR 5.63) and severe hyperglycemia (OR 8.11), daytime hypoglycemia (OR 1.48), and hypoglycemia-related fasting interruption (OR 1.77). Severe hypoglycemia rates did not differ significantly between HbA1c groups.Higher pre-Ramadan HbA1c was associated with lower fasting participation and a greater risk of hyperglycemia and hypoglycemia-related complications. These results support the use of the current HbA1c thresholds in Ramadan risk assessment and emphasize the importance of optimizing glycemic control and providing targeted education before Ramadan.
Keywords: Ramadan fasting; T2 diabetes mellitus; HbA1c; glycemic control; hypoglycemia; hyperglycemia; risk assessment; DAR risk calculator